Role of High Physical Fitness in Deterioration of Male Sexual Function in Japanese Adult Men. Issue 3 (8th May 2019) - Kumagai, Hiroshi; Yoshikawa, Toru; Myoenzono, Kanae; Kosaki, Keisei; Akazawa, Nobuhiko; Tanahashi, Koichiro; Tagawa, Kaname; Zempo-Miyaki, Asako; Maeda, Seiji
Male sexual function is regulated by vascular function and impaired vascular function is closely related with erectile dysfunction (ED). Vascular functions are positively influenced by physical fitness (i.e., aerobic capacity, muscle strength, and flexibility). The detailed associations between physical fitness and male sexual function remain poorly understood. The present study aimed to clarify the influence of physical fitness on male sexual function. In 177 adult men, peak oxygen consumption (VO2 peak ), handgrip strength (HGS), and sit and reach were measured as indices of physical fitness. Arterial stiffness and erectile function were assessed by carotid–femoral pulse wave velocity (cfPWV) and the International Index of Erectile Function 5 (IIEF5) questionnaire, respectively. IIEF5 score was significantly correlated with VO2 peak ( rs = 0.52), HGS ( rs = 0.37), and cfPWV ( rs = −0.44); and multivariate linear regression analyses showed that VO2 peak, HGS, and cfPWV were significantly associated with IIEF5 score after considering confounders. The receiver operator characteristic curve analysis suggested that the cutoff values for predicting ED were 29.0 ml/min/kg for VO2 peak and 39.3 kg for HGS. The IIEF5 score was the highest in the subjects with the values of both VO2 peak and HGS were higher than their respective cutoff values, while the IIEF5 score was the lowest in the subjects with the values of both VO2 peak and HGS were lower than their respective cutoff values. These results suggest that the maintenance of high aerobic capacity and muscular strength may offset deterioration of male sexual function.